New Agrilus Curtis (Coleoptera: Buprestidae) from México and Costa Rica mimicking parasitic wasps - Hespenheide, Henry A. (Zootaxa, 2010)
Three species of the genus Agrilus are described: A. bellamyi New Species from México, and A. braconoides New Species and A. lucindae New Species from Costa Rica. The male of Agrilus braconicoloratus Hespenheide from México is also described for the first time. These four species are hypothesized to be mimics of wasps in the family Braconidae, some of which are parasitic on wood-boring beetles. The mimicry complex is briefly described and discussed for Costa Rica and Panamá and probably involves both Mullerian and Batesian relationships with other beetles (Cerambycidae, Cleridae, and baridine Curculionidae) and Hymenoptera (Ichneumonidae and Mutillidae), predatory Heteroptera (Reduviidae), Diptera (Tipulidae), and other taxa. Examples are also given for South America and the Old World.